Aesthetic management of molar-incisor hypomineralization - Juliana Feltrin de Souza; Camila Maria Bullio Fragelli; Manuel Restrepo; Amanda Mahammad Mushashe; Estela Maris Losso; Leonardo Fernandes da Cunha (Revista Sul-Brasileira de Odontologia, 2015)
Molar-incisor hypomineralization (MIH) has been challenging for clinical practice. The term refers to an enamel defect that affects permanent molars and often permanent incisors. This defect may result in high sensibility, coronal destruction of the molars, aesthetic problem when incisors are affected, which can jeopardize the child`s emotional and psychological development. Objective: The aim of this paper is to report two cases in which a conservative approach was adopted using new technologies for direct restorative treatment of incisor with MIH opacities. Case report: Patients aged 11 and 12 years-old attended to the clinics of the School of Dentistry (Sao Paulo State University – Unesp) complaining about the appearance of incisors due to the presence of opacities on the labial surface. The cases were diagnosed as MIH, presenting enamel defects on the permanent molars and incisors. Direct restorations were carried out with minimal removal of the opacities using CVD diamond tip (CVDentus, São José dos Campos, São Paulo, Brazil) coupled to an ultrasonic device (CVDentus, São José dos Campos, São Paulo, Brazil) and direct restorations with composite resin. The result of the restorative treatment was satisfactory in both cases, with children showing immediate satisfaction. Conclusion: The incisors affected by MIH should be treated to improve the child`s self-esteem and avoid negative effects on their psychology development. The aesthetic treatment of the incisors should be conservative, since the replacements of restorations are needed throughout life.